KEDUDUKAN JAMINAN FIDUSIA DALAM PERJANJIAN PEMBIAYAAN KONSUMEN DITINJAU DARI HUKUM EKONOMI ISLAM DAN HUKUM POSITIF DI INDONESIA - Abdul Atsar (Fakultas Syariah Institut Agama Islam Negeri Palu, 2022)
This study aims to examine the legal aspects regarding the position of fiduciary guarantees in murabahah financing agreements. The position of guarantees in financing agreements according to Islamic economic law states that guarantees in the practice of financing institutions are allowed because in order to maintain the trust of debtors, Islamic financial institutions must establish the principle of prudence and look at the condition of society that has experienced a shift in terms of commitment to moral values ​​such as trust and honesty. Consumer financing agreements basically do not emphasize the collateral aspect. However, because consumer finance is a business institution, consumer finance companies in financing activities cannot be separated from risk, to avoid risk, consumer finance usually asks for certain guarantees as guarantees in financing. The main guarantee in a financial institution is in the form of trust, the main guarantee is in the form of goods financed on a fiduciary basis, and additional guarantees in the form of power to sell and others. Financing based on sharia principles but does not apply sharia guarantees is an act that is contrary to sharia principles.